Leadership Style, Motivation, and Communication on Organizational Commitment and Employee Performance in the Rokan Hulu Regional General Hospital - Yuli Marliza; Nyoto; Sudarno (Journal of Applied Business and Technology, 2022)
This study aimed to determine the effect of leadership style, motivation, and communication on organizational commitment and employee performance at the Rokan Hulu General Hospital. The data collection techniques were interviews, questionnaires, and employee data. The population in this study were employees of the Rokan Hulu General Hospital, the sample selection used the total sample method, with a total sample of 114 people. The data analysis technique used Structural Equation Modeling (SEM PLS) and Smart PLS. The results showed that leadership style had no significant effect on employee job satisfaction, leadership style had no significant effect on employee performance, motivation had no significant effect on organizational commitment, communication had no significant effect on employee performance, and leadership style had a significant effect on organizational commitment, significant effect on employee performance, communication has a significant effect on organizational commitment, and motivation has a significant impact on employee performance.